2015
DOI: 10.1128/jcm.00143-15
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Epidemiology of Clostridium botulinum Isolates from Temporally Related Cases of Infant Botulism in New South Wales, Australia

Abstract: dInfant botulism is a potentially life-threatening paralytic disease that can be associated with prolonged morbidity if not rapidly diagnosed and treated. Four infants were diagnosed and treated for infant botulism in NSW, Australia, between May 2011 and August 2013. Despite the temporal relationship between the cases, there was no close geographical clustering or other epidemiological links. Clostridium botulinum isolates, three of which produced botulism neurotoxin serotype A (BoNT/A) and one BoNT serotype B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…Local evolution of strains and commercial exchanges of food products with other countries might account for the diversity of French C. botulinum strains. Recent investigations also show similar C. botulinum diversity in other countries such as in Italy ( Giordani et al 2015 ), Japan ( Kenri et al 2014 ), Australia ( McCallum et al 2015 ) and other parts in the world (reviewed in Carter and Peck 2015 ; Hill et al 2015 ; Smith, Hill, Raphael 2015 ; Smith, Hill, Xie, et al 2015 ). Thereby, the BoNT-producing clostridia share a high genetic plasticity the mechanisms of which including acquisition or loss of genetic materials by mobile genetic elements (plasmids, phages) and genetic rearrangements by insertion, recombination, mutation events are not yet fully understood.…”
Section: Discussionmentioning
confidence: 66%
“…Local evolution of strains and commercial exchanges of food products with other countries might account for the diversity of French C. botulinum strains. Recent investigations also show similar C. botulinum diversity in other countries such as in Italy ( Giordani et al 2015 ), Japan ( Kenri et al 2014 ), Australia ( McCallum et al 2015 ) and other parts in the world (reviewed in Carter and Peck 2015 ; Hill et al 2015 ; Smith, Hill, Raphael 2015 ; Smith, Hill, Xie, et al 2015 ). Thereby, the BoNT-producing clostridia share a high genetic plasticity the mechanisms of which including acquisition or loss of genetic materials by mobile genetic elements (plasmids, phages) and genetic rearrangements by insertion, recombination, mutation events are not yet fully understood.…”
Section: Discussionmentioning
confidence: 66%
“…Isolates from the patient and their home environment were frequently present in the same clade, indicating the probable source of infective spores [62]. A study of four time-coincident infant botulism cases in Australia revealed that the four Group I strains involved were related but not identical, suggesting that they had not come from a single source, but had diverged from a common ancestor many hundreds of years ago [63]. It is likely that whole genome sequencing and other molecular techniques will be of great value in future microbial forensic studies [64, 65].…”
Section: Impact Of Genomic Diversity On Food Safetymentioning
confidence: 99%
“…Botulinum neurotoxin-producing Clostridia have been identified from all continents except Antarctica. These microbes are often isolated from samples associated with human botulism cases (food poisonings or intestinal or wound infections), and researchers have also isolated BoNT-producing Clostridia from environmental samples including soils, honey, aquatic sediments and plants [ 17 , 23 – 34 ]. The distribution of serotypes A–G can be obtained from publications based upon characterization of strains within different culture collections, environmental sampling and reported botulism cases.…”
Section: Introductionmentioning
confidence: 99%